Effects of Testosterone on Mixed Muscle Protein Synthesis and Proteome Dynamics During Energy Deficit. (29th May 2020) - Pasiakos, Stefan; Shankaran, Mahalakshmi; Berryman, Claire; Margolis, Lee; Lieberman, Harris; Karl, J Philip; Young, Andrew; Montano, Monty; Matthews, Marcy; Bizieff, Alec Alec; Nyangau, Edna; Mohammed, Hussein; et al.
Abstract: Objectives: Short-term energy deficit reduces acute measures of mixed muscle protein synthesis (MPS) and suppresses the hypothalamic-pituitary axis and endogenous testosterone synthesis. We hypothesized that testosterone supplementation could mitigate the effects of energy deficit on MPS. We conducted a randomized, double-blind, placebo-controlled trial to determine the effects of 28 days of tightly-controlled severe energy deficit (deficit 55% of total energy requirements) on measures of mixed-MPS and proteome-wide protein dynamics in non-obese men either given 200 mg testosterone enanthate (Testosterone, n = 24) or placebo (Placebo, n = 26) injections per week. Methods: Participants received daily aliquots of deuterated water ( 2 H2 O) for 42 consecutive days (14-d weight maintenance period followed by 28-d energy deficit). Muscle biopsies were collected at rest in a fasted state at the end of the weight maintenance phase (PRE) and at the middle (MID) and end (POST) of the 28-d energy deficit. Mixed-MPS and proteome-wide protein fractional synthesis rates (FSR) were quantified. Changes over time and differences between Testosterone and Placebo were determined for mixed-MPS, and cross-sectional comparisons between Testosterone and Placebo were performed at MID and POST for proteome dynamics. Results: In both Testosterone and Placebo, mixed-MPS were 40% and 33% lower ( P < 0.0005) at MID and POST energy deficit, respectively, compared to PRE, with no differences between groups or between MID and POST. Proteome-wide FSR of individual muscle proteins did not differ between Testosterone and Placebo at any time point. However, at POST, the number of individual proteins with higher FSR in Testosterone than Placebo was significant by 2-tailed binomial test ( P < 0.05), with values ranging from 20–32% higher FSR for myofibrillar, mitochondrial and cytosolic proteins. Conclusions: Findings confirm the pronounced effect of short-term severe energy deficit on mixed-MPS and suggest the anabolic suppression occurs largely independent of testosterone. However, proteome-wide protein dynamics may reveal a novel time sensitive signal by which supplemental testosterone triggers a delayed increase in MPS, providing a synthetic mechanism for muscle mass preservation or accrual. Funding Sources: Supported by DHP JPC-5/MOMRP; authors' views not official U.S. Army or DoD policy.